Development of a novel composite resin for dissolved divalent mercury measurement using diffusive gradients in thin films. (July 2020) - Yao, Heng; Zhao, Yujie; Lin, Che-Jen; Yi, Fengjiao; Liang, Xuefeng; Feng, Xinbin
Abstract: In this work, a composite resin gel incorporating thiol-modified metal double hydroxide ( TM-MDH) nanoparticles is developed for application in diffusive gradients in thin films (DGT) devices to sample and concentrate divalent Hg (Hg(II)) in water and sediment samples. The DGT device uses the TM-MDH resin as a sorption layer and an agarose gel as a diffusive layer. Complete digestion of the TM-MDH resin after sampling can be achieved in 5 mL of 12 N HCl solution for 30 min for direct aqueous Hg(II) analysis. The recovery of Hg(II) uptake onto the resin in aqueous solution reaches 95.4 ± 1.9%. The effect of ionic strength and pH on the performance of DGT device for Hg(II) is assessed. It is found that there is no significant difference on Hg(II) uptake over a pH range of 3.5–8.5 and an ionic strength range of 1–500 mM NaCl. The diffusion coefficient of Hg(II) at 25 °C was estimated to be 9.48 × 10 −6 cm 2 /s at 50 μg/L solution. The sorption capacity of TM-MDH-DGT for Hg(II) reaches 41.0 μg/cm 2 . Field validations performed in reservoir water and in contaminated paddy soil demonstrate that the developed TM-MDH DGT device can accurately determine Hg(II) concentrations in these samples and outperform traditional sampling methods for both high and low Hg(II) concentrations. Graphical abstract: Image 1 Highlights: A novel composite resin has been developed for divalent mercury measurement using DGT devices. The resin is a highly uniform substrate and easily digestible for divalent mercury determination. The new resin equipped DGT device can accommodate a wide range of environments. The DGT method is reliable and cost-effective for measuring divalent mercury in water and sediments.